Preconditioning of Summer Melt Ponds From Winter Sea Ice Surface Temperature. Issue 4 (22nd February 2023) - Thielke, Linda; Fuchs, Niels; Spreen, Gunnar; Tremblay, Bruno; Birnbaum, Gerit; Huntemann, Marcus; Hutter, Nils; Itkin, Polona; Jutila, Arttu; Webster, Melinda A.
Abstract: Comparing helicopter‐borne surface temperature maps in winter and optical orthomosaics in summer from the year‐long Multidisciplinary drifting Observatory for the Study of Arctic Climate expedition, we find a strong geometric correlation between warm anomalies in winter and melt pond location the following summer. Warm anomalies are associated with thinner snow and ice, that is, surface depression and refrozen leads, that allow for water accumulation during melt. Warm surface temperature anomalies in January were 0.3–2.5 K warmer on sea ice that later formed melt ponds. A one‐dimensional steady‐state thermodynamic model shows that the observed surface temperature differences are in line with the observed ice thickness and snow depth. We demonstrate the potential of seasonal prediction of summer melt pond location and coverage from winter surface temperature observations. A threshold‐based classification achieves a correct classification for 41% of the melt ponds. Plain Language Summary: We compare winter surface temperatures from an infrared camera with summer photographs of sea ice with melt ponds. The datasets were recorded from a helicopter during the Multidisciplinary drifting Observatory for the Study of Arctic Climate expedition. Melt ponds form on sea ice in summer when the snow melts and water accumulates in the lower locations on the ice floes. Melt ponds are very important for the Arctic energy budget because they strongly change the sea ice brightness and thus the amount of solar energy absorbed by the ice. We find surface characteristics with similar size and location between warmer areas in winter and the location of melt ponds in summer. For a better process understanding, we calculate the surface temperature with a simple model and find that the warm temperature anomalies are due to thinner ice and snow. Stronger warm temperature anomalies appear in new cracks in the ice which are covered with newly formed, thin ice. With a temperature‐based classification, we are able to estimate the summer melt pond fraction. Key Points: Winter warm surface temperature anomalies are co‐located with melt pond locations in the following summer Warm anomalies appear in refrozen leads, in refrozen melt ponds, and in troughs between ridges, due to thinner snow and ice We show the potential for prediction of summer melt pond fraction from winter surface temperatures